Theoretical and Methodological Foundations for Developing University Students' Intercultural Competence by Means of Traditional Music of the Peoples of the World - Yulia S. Ovchinnikova (Peoples' Friendship University of Russia (RUDN University), 2024)
The need to take into account cultural diversity in music education is recognized today in scientific communities of different countries. A relevant area of foreign research is the conceptualization of multicultural music education and the methodology for developing students' intercultural competence. Despite the fact that the multicultural focus of music educational programs has been outlined at the international and national levels, the theoretical and methodological foundations for developing students' intercultural competence through the study of music of different nations remain underdeveloped. Most foreign studies reveal either the conceptual focus of multicultural music education, or the experimental one, showing the developing potential of a multicultural approach to teaching music in individual cases. The accumulation of positive experience in intercultural interaction through ethnomusical dialogue in world practice necessitates its further theoretical and methodological understanding. The author of this article compares and generalizes foreign and domestic experience in using different methods for developing students' intercultural competence by means of music, as well as to typologize the tested methods within the framework of four fundamental approaches, namely ethnomusicological (musical-cultural), subject-activity, anthropological (musical-psychological) and personality-oriented (humane-personal) ones. Considering that there are very few studies to date that demonstrate the effectiveness of these approaches in multicultural music education, the author also attempts to theoretically substantiate them based on foreign and domestic experience. In addition, the article offers a number of conceptual and theoretical justifications for the comprehensive application of these approaches in developing students' intercultural competence by means of multicultural music practices. Systematization of international experience will make it possible to consider the construct of intercultural competence in an expanded, integrative dimension with regard to multicultural music education, which creates a basis for building theoretical and methodological relationships between educational categories of different levels: from conceptual and methodological approaches to methods of their implementation and the expected result, i.e., the development of various components of intercultural competence.